On Reverse Super Edge Magic Total Labeling of Subdivided Trees - Abdul Raheem (Scientific Inquiry and Review, 2018)
A reverse edge magic total labeling of a graph ???? is a one-to-one map ????∶????(????)∪????(????)→1,2,…,|????(????)∪????(????)|=[1,|????(????)∪????(????)|] with the property that there is an integer constant ???? such that ????(????????)−(????(????)+????(????))????????∈????(????)⁄=????. If (????(????))=[1,|????(????)|] then the reverse edge magic labeling is called reverse super edge-magic labeling. In this paper we will formulate the reverse edge magic labeling of two subclasses of trees.